Faktor-faktor yang berhubungan dengan kejadian unintended pregnancy pada remaja - Lidya Yulanda Sari; Lutfi Nurdian Asnindari (Universitas Aisyiyah Yogyakarta, 2016)
Abstract: This research aims to study factors related to the eventunintended pregnancy adolescent. The analysis used is the chi squaretest. Results of research on the variable level of knowledge about theunintended pregnancy in the case group and 46.7% less category 66.7%of control group both categories. In variable teenage promiscuity themajority of the cases 86.7% less category, 40% of the control groupboth categories. In variable parenting parents, the majority of the cases66.7% less category, 73.3% of the control group both categories. Inthe variable of mass media, the majority of the cases 14% less diversecategories, 33.3% of control group is very diverse categories. There isa relationship between the level of knowledge, relationships teens,parenting parents, and the media with a value of ñ value (0.000) á(0.05).